PENGEMBANGAN PARIWISATA DAM RAMAN KOTA METRO: SINERGISITAS PEMERINTAH KOTA DAN KOMUNITAS MASYARAKAT - Danar, Danar; Widodo, Wahyu (Administratio, 2018)
ABSTRACT. The city has several tourist attractions that can be visited by tourists, one of which is the Raman Dam. This article aims to describe the role of the Youth, Sports and Tourism Service, the Society of Unified Communities (PAMBERS), and the IUD Community in synergizing developing the Raman DAM as a new tourist attraction in Metro City. Using a qualitative descriptive approach the results of the study concluded that the Office had a role in providing access to transportation, conducting official visits, holding art attractions and promotions as well as programs for tourism books. PAMBERS has played a role in changing the image of the Raman DAM area as a vulnerable area. While the ADKR community promotes through social media.